The negative impact of a sense of community on consumers: focusing on trash talk - Hato, Masahiko (Frontiers in Communication, 2025)
In today’s hyperconnected digital landscape, brands cultivate a sense of community among consumers to enhance engagement and loyalty. While such efforts can foster positive brand relationships, they may also lead to unintended negative consequences. This study examines how a strong sense of community among brand consumers can contribute to hostile behaviors, specifically trash talk against rival brands. Drawing on social identity theory, we hypothesize that a sense of community fosters trash talk, mediated by inter-brand and inter-consumer rivalry. A survey of Japanese consumers (N = 310) reveals that while inter-brand rivalry does not significantly drive trash talk, inter-consumer rivalry plays a critical role. Consumers with a sense of community are likely to develop inter-consumer rivalry, which in turn amplifies trash talk. Moreover, a sequential mediation effect is identified, where a sense of community heightens inter-brand rivalry, which subsequently fuels inter-consumer rivalry, leading to trash talk. These findings underscore the risks associated with fostering a sense of community in brand management. While strengthening consumer connections can enhance loyalty, it may also intensify competitive hostility, potentially harming brand equity. This study expands existing research by highlighting the dual nature of a sense of community and its implications for brand strategy.